FERTILITY STATUS EVALUATION AND SOIL CHEMICAL PROPERTIES EFFECT ON JABON (Neolamarckia cadamba (Roxb. Bosser)) TREE GROWTH IN CIKULUR, SINGAJAYA, AND SUKANAGARA DISTRICT - Thalika (Nim : 11514011), Firda
Through soil chemical properties, can be known Fertility Status of a land and determine its effect on the growth of both diameter, height and volume of a tree. This study aims to determine the fertility status and soil chemical properties and their effect on the annual average growth rate of Jabon trees (Neolamarckia cadamba) in Cikulur, Singajaya, and Sukanagara Districts. For the sampling of trees, purposive sampling method was used where each location was made of three circular plots measuring 0.1 ha with a radius of 17.8 m. Whereas for soil sampling is done by a composite method with a diagonal system, then soil testing is carried out in the laboratory and analyzed for soil fertility status based on soil chemical characteristics and soil fertility status from Lembaga Pusat Penelitian Tanah (1995). The results showed the value of soil chemical properties in 3 research locations, namely Cikulur, Singajaya, and Sukanagara was for pH H2O 4,6-5,1, then for pH KCl 3,5-4,3; C-Organic 2,44-5,87%; N-Total 0,23-0,57%; Available-P 2-2,6 ppm; P-Total 29,73-91,77 mg/100g; K-Total 11,93-33,1 mg/100g; Available-K 86,5-333,4 ppm; Ca 3,79-5,44 cmol/kg; Mg 1,53-3,81 cmol/kg; Cation Exchange Capacity 11,75-20,14 cmol/kg; and Base Saturation 39-57%. The soil fertility status in Neolamarckia cadamba stands in Singajaya District has a moderate fertility status, and for Cikulur and Sukanagara Districts it has low fertility status. The components of soil chemical properties that affect the diameter Mean Annual Increament (MAI) of Neolamarckia cadamba stand are Cation Exchange Capacity (CEC) with the regression equation, Height MAI = 1.398 + 0.95 (CEC). Whereas the Height MAI and volume of Neolamarckia cadamba stand was affected by pH H2O, with the regression equation DBH MAI = -2.420 + 1.151 (pH H2O) and Volume MAI = -0.197 + 0.048 (pH H2O).